The Libyan Economy Economic Diversification and International Repositioning - Otman, Waniss A.; Karlberg, Erling; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2007)
This book delivers a thorough and essential analysis of current economic policy, transformation and legislative changes in Libya. The authors have comprehensively surveyed and analysed the country$1 (Bs social development and trends, its current infrastructural deficit, and its often controversial foreign relations. Thereby, they answer many questions about Libya$1 (Bs distinctive society and economic system and explain the necessity for the major restructuring of the Libyan economy which is currently in process. The book makes extensive use of previously unavailable economic and social data and thus allows a unique insight into a fascinating country on its way to reposition itself in a regional and international context.s
An Introduction to Libya -- Libya$1 (Bs Foreign Policy and External Relations -- The Libyan Legal System and Key Recent Legislation -- Social Policy and Trends -- Infrastructure in Libya -- The Rationale for Libyan Privatization -- Libya$1 (Bs Investment Potential and Trade Blocs -- Economic Reform and Diversification -- The Libyan Energy and Mining Sector -- Libyan Environmental Law and Issues -- The Forces Shaping Libya$1 (Bs Future -- Assessing Libya$1 (Bs Post-sanctions Initiatives.s
Keywords: Political science; Economic policy; Development economics; Economics; Economic Policy; Development Economics; Political Science; Electronic books